Thermodynamic simulation calculation method for calcium carbonate crystal form regulation in carbon mineralization process

By using thermodynamic simulation calculations to regulate the crystal form of calcium carbonate, the problem of unpredictable crystal form ratios in carbon mineralization technology was solved, thereby improving the mechanical properties and CO2 capture efficiency of cement-based materials.

CN121034443APending Publication Date: 2025-11-28HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511565323.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing carbon mineralization technologies have difficulty accurately predicting and controlling the proportion of calcium carbonate crystal forms, which affects the mechanical properties of cement-based materials.

Method used

Thermodynamic simulation was used to establish a thermodynamic database by determining initial conditions, correcting for temperature and ion doping effects, calculating the proportion of calcium carbonate crystal forms, and using inorganic and organic modifiers to regulate the calcium carbonate crystal forms.

Benefits of technology

This approach enables proactive design of calcium carbonate crystal forms, improves the flexural strength and toughness of carbonized mineral products, optimizes CO2 input and temperature parameters, and saves R&D resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121034443A_ABST
    Figure CN121034443A_ABST
Patent Text Reader

Abstract

The invention discloses a thermodynamic simulation calculation method for calcium carbonate crystal form regulation in a carbon mineralization process, and belongs to the technical field of material thermodynamic simulation calculation and carbon mineralization. The method comprises the following steps: determining the oxide composition, CO2 input quantity, temperature and crystal form regulator concentration of the cement-based material; correcting the influence of temperature and ion doping on thermodynamic data; calculating the solid phase composition and ion concentration of the carbonized product based on a Gibbs free energy minimization principle; calculating the influence of the regulator on free energy and surface free energy of calcium carbonate bodies with different crystal forms; and finally obtaining the total amount of calcium carbonate and different crystal form proportions. By regulating and controlling the proportion of aragonite type calcium carbonate, the bending strength and toughness of the carbon mineralized product are improved, and a theoretical basis is provided for crystal form design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials thermodynamic simulation and carbon mineralization technology, specifically relating to a thermodynamic simulation method for controlling the crystal form of calcium carbonate during carbon mineralization. Background Technology

[0002] In cement production, over 60% of carbon emissions originate from the decomposition of mineral carbonates, and its reverse reaction—carbon mineralization—has significant carbon sequestration potential. Carbon mineralization technology utilizes CO2-containing industrial waste gases (such as those from cement plants, steel mills, and power plants) to react with calcium / magnesium minerals in cement-based materials, forming stable calcium carbonate and improving material strength. It is currently one of the most promising CO2 sequestration technologies for industrial-scale application. For example, LafargeHolcim Group in Switzerland, Heidelberg Cement in Germany, and the collaborative project between Hunan University and Huaxin Cement in my country have all promoted the industrial application of this technology.

[0003] Calcium carbonate is the main product of carbon mineralization (content 60-75%), and its crystal forms include cubic calcite, fibrous aragonite, and metastable spherulite. Due to differences in microstructure, different crystal forms significantly affect the performance of the finished products: aragonite, due to its large aspect ratio and ease of forming whisker structures, can improve the flexural strength and toughness of the material; while calcite is more stable under standard thermodynamic conditions. Existing carbon mineralization technologies mainly focus on increasing the degree of mineralization to retain more CO2, but pay insufficient attention to the control of calcium carbonate crystal forms. This stems from the complex raw material composition and concurrent hydration / carbonation reactions during the carbon mineralization process of cement-based materials, making it difficult to accurately predict and control the proportion of different calcium carbonate crystal forms. Ignoring the kinetic process and directly calculating the product composition based on thermodynamics is an effective strategy, but to date, there are no reports on thermodynamic calculation methods involving the control of calcium carbonate crystal forms during the carbon mineralization process of cement-based materials. Summary of the Invention

[0004] The technical problem this invention aims to solve is how to predict and control the crystal form ratio of calcium carbonate during carbon mineralization through thermodynamic simulation calculations to improve the mechanical properties of the product. To address this problem, this invention provides a thermodynamic simulation calculation method for controlling the crystal form of calcium carbonate during carbon mineralization. This method can calculate the proportion of different calcium carbonate crystal forms in the product based on the carbon mineralization conditions, or inversely deduce suitable carbon mineralization conditions based on the designed required calcium carbonate crystal form ratio. A thermodynamic model is established to reveal the thermodynamic mechanism of calcium carbonate crystal form transformation during carbon mineralization, providing a theoretical basis for the calcium carbonate crystal form transformation during the carbon mineralization process.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: A thermodynamic simulation calculation method for the regulation of calcium carbonate crystal form during carbon mineralization includes the following steps: Step S1: Determine the initial conditions, including the oxide composition of the cement-based material, the amount of carbon dioxide input, the temperature, and the concentration of the crystal form regulator; Step S2: Correct the effects of temperature and ion doping on the thermodynamic data of calcium carbonate crystal form and establish a thermodynamic database; Step S3: Based on the principle of minimizing Gibbs free energy, calculate the solid composition, ion concentration, pH change and porosity of the carbon mineralization products of cement-based materials. Step S4: Calculate the effect of the crystal form regulator on the bulk free energy and surface free energy of calcium carbonate crystal form; Step S5: Calculate the proportion of calcium carbonate crystal form in the carbon mineralization product.

[0006] Optionally, in step S1, the crystal form regulator includes inorganic regulators represented by magnesium salts and organic regulators represented by alkanolamines.

[0007] Optionally, in step S2, the calcium carbonate crystal forms include calcite, aragonite, and spherulite.

[0008] Optionally, in step S2, the thermodynamic database is established based on the following method: The database uses a combination of PSI / Nagra and Cerndata18 open-source databases. The Gibbs generation free energy and enthalpy of formation of calcite and aragonite partially substituted with magnesium ions were quantified by combining basic polyhedral units. The Gibbs generation free energy of calcite and aragonite as a function of temperature was calculated based on the Harper equation.

[0009] Optionally, in step S3, the solid phase composition and ion concentration are calculated using the open-source thermodynamic software GEMSELEKTOR, and the final generated phase is determined by the principle of minimizing Gibbs free energy. The solid phase composition includes mass variations of calcite, aragonite, silica gel, hydrated magnesium silicate gel, magnesium calcite, ferrophosphate, and kaolinite. The ion concentration includes Ca in the liquid phase. 2+ Mg 2+ K + Na + CO3 2- HCO3 - SO4 2- OH - H + Mg(HCO3) + Ca(HCO3) + Ca(HSiO3) + The concentration change.

[0010] Optionally, when the crystal form regulator is an inorganic regulator, step S4 includes: Calculate the change in volume free energy caused by magnesium ion substitution for calcium ions in calcite; Calculate the effective magnesium ion concentration in calcium carbonate clusters; The relationship between the degree of penetration and the magnesium-to-calcium ratio and temperature was fitted.

[0011] Optionally, when the crystal form regulator is an organic regulator, step S4 includes: The adsorption capacity of organic regulators on CSH gels with different calcium-to-silicon ratios was quantified using the CSHQ model. The effect of calcium carbonate layer thickness on adsorption coverage was corrected based on the Temkin II adsorption model. The effects of organic modifiers on surface energy and critical nucleation energy were calculated.

[0012] Optionally, the method is applicable to controlling the total amount and relative proportion of calcite, aragonite and aragonite in carbon mineralization products to improve the flexural strength and toughness of carbon mineralization products.

[0013] The beneficial effects of this invention are as follows: 1. This invention uses thermodynamic calculations to predict the proportions of calcite, aragonite, and aragonite under different carbon mineralization conditions, enabling proactive design of the calcium carbonate crystal structure. In particular, it can directionally increase the proportion of aragonite whiskers with high aspect ratios, thereby solving the problems of low flexural strength and poor toughness in carbon mineralized products.

[0014] 2. This invention can accurately calculate the critical values ​​of parameters such as CO2 input and temperature. For example... Figure 4 As shown, the model can predict the inflection point of CO2 absorption rate (M(CO2) / M(PC)=0.48), avoiding the escape caused by excessive CO2 input, and preventing energy waste caused by excessively high temperature.

[0015] 3. This invention quantitatively elucidates the mechanism of action of inorganic / organic regulators: inorganic regulators (such as magnesium salts) change the bulk free energy through ion doping; organic regulators (such as alkanolamines) reduce the surface free energy through surface adsorption, providing a theoretical basis for crystal form regulation.

[0016] 4. When the composition of raw materials such as cement and fly ash fluctuates, this invention only requires adjusting the input oxide composition parameters and can obtain the crystal ratio under new conditions without repeating experiments, thus significantly saving research and development resources. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 This is the thermodynamic calculation process and technical roadmap provided by the present invention.

[0018] Figure 2 This is a comparison chart of experimental and calculated results for different magnesium chloride concentrations and litharge ratios in Example 3 of the present invention.

[0019] Figure 3 This is a comparison chart of the experimental and calculated results of different CO2 input amounts and limestone ratios in Embodiment 3 of the present invention.

[0020] Figure 4 This is a comparison chart of the experimental and calculated results of CO2 absorption rate under different CO2 input amounts in Example 3 of the present invention.

[0021] Figure 5 This is a comparison chart of experimental and calculated results for different MEA concentrations and calcite ratios in Example 4 of the present invention.

[0022] Figure 6 This is a comparison chart of the experimental and calculated results of the aragonite ratio at different temperatures in Example 4 of the present invention.

[0023] Figure 7 This is a comparison chart of the experimental and calculated results of different magnesium chloride concentrations in references [1-4] in Example 5 of this invention.

[0024] Figure 8 This is a comparison chart of the experimental and calculation results of different PAA concentrations in Reference [5] in Example 5 of this invention.

[0025] Figure 9 This is a comparison chart of the experimental and calculation results of different PAM concentrations in references [6-8] in Example 5 of this invention.

[0026] Figure 10 This is a comparison chart of the experimental and calculation results of different PAV concentrations in reference [9] in Example 5 of this invention.

[0027] Figure 11 This is a comparison chart of the experimental and calculation results at different temperatures in references [5] and [10-12] of Embodiment 5 of the present invention; Figure 12 These are electron microscope images of aragonite provided by this invention; Figure 13 These are electron microscope images of calcite provided by this invention; Figure 14 This is an electron microscope image of aragonite provided by the present invention. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative positional relationship and movement of each component in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indication will also change accordingly.

[0030] Furthermore, in this invention, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0031] In this invention, unless otherwise explicitly specified and limited, the terms "connection," "fixed," etc., should be interpreted broadly. For example, "fixed" can mean a fixed connection, a detachable connection, or an integral part; it can mean a mechanical connection; it can mean a direct connection or an indirect connection through an intermediate medium; it can mean the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0032] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0033] Please see Figure 1 As shown, this embodiment of the invention provides a thermodynamic simulation calculation method for the regulation of calcium carbonate crystal form during carbon mineralization, including the following steps: Step S1: Determine the initial conditions, including the oxide composition of the cement-based material, the amount of carbon dioxide input, the temperature, and the concentration of the crystal form regulator; Step S2: Correct the effects of temperature and ion doping on the thermodynamic data of calcium carbonate crystal form and establish a thermodynamic database; Step S3: Based on the principle of minimizing Gibbs free energy, calculate the solid composition, ion concentration, pH change and porosity of the carbon mineralization products of cement-based materials. Step S4: Calculate the effect of the crystal form regulator on the bulk free energy and surface free energy of calcium carbonate crystal form; Step S5: Calculate the proportion of calcium carbonate crystal form in the carbon mineralization product.

[0034] In step S1, the crystal form regulators include inorganic regulators represented by magnesium salts and organic regulators represented by alkanolamines.

[0035] In step S2, the calcium carbonate crystal forms include calcite, aragonite, and spherulite.

[0036] The thermodynamic database was established based on the following methods: The database uses a combination of PSI / Nagra and Cerndata18 open-source databases. The Gibbs generation free energy and enthalpy of formation of calcite and aragonite partially substituted with magnesium ions were quantified by combining basic polyhedral units. The Gibbs generation free energy of calcite and aragonite as a function of temperature was calculated based on the Harper equation.

[0037] In step S3, the solid phase composition and ion concentration were calculated using the open-source thermodynamic software GEM SELEKTOR, and the final generated phase was determined by minimizing the Gibbs free energy. The solid phase composition includes mass variations of calcite, aragonite, silica gel, hydrated magnesium silicate gel, magnesium calcite, ferrophosphate, and kaolinite. The ion concentration includes Ca in the liquid phase. 2+ Mg 2+ K + Na + CO3 2- HCO3 - SO4 2- OH - H + Mg(HCO3) + Ca(HCO3) + Ca(HSiO3) + The concentration change.

[0038] When the crystal form regulator is an inorganic regulator, step S4 includes: Calculate the change in volume free energy caused by magnesium ion substitution for calcium ions in calcite; Calculate the effective magnesium ion concentration in calcium carbonate clusters; The relationship between the degree of penetration and the magnesium-to-calcium ratio and temperature was fitted.

[0039] When the crystal form regulator is an organic regulator, step S4 includes: The adsorption capacity of organic regulators on CSH gels with different calcium-to-silicon ratios was quantified using the CSHQ model. The effect of calcium carbonate layer thickening on adsorption coverage was corrected based on the Temkin II model. The effects of organic modifiers on surface energy and critical nucleation energy were calculated.

[0040] The method described above is applicable to controlling the total amount and relative proportion of calcite, aragonite and aragonite in carbon mineralization products, so as to improve the flexural strength and toughness of carbon mineralization products.

[0041] The following detailed description of the thermodynamic simulation calculation method for calcium carbonate crystal form regulation during the carbon mineralization process provided by the present invention uses specific embodiments.

[0042] Example 1 When using inorganic crystal form modifiers, such as magnesium salts, the thermodynamic simulation calculation method for calcium carbonate crystal form regulation during carbon mineralization is as follows: First, based on the idea of ​​characterizing the thermodynamic properties of carbonate minerals by combining their basic polyhedral units, the Gibbs generation free energy of calcite and aragonite partially replaced by magnesium is quantified, as shown in Equation (1).

[0043] (1) in, It is a building block of matter; for example, calcium carbonate is composed of CaO and CO2. It is a constituent unit i The contribution factor to the standard Gibbs free energy of this substance; is a natural number greater than 1; the thermodynamic parameters of different calcium carbonate crystal forms are shown in Table 1.

[0044] Table 1. Thermodynamic parameters of different calcium carbonate crystal forms (298.15 K) Based on the difference in standard Gibbs free energy between calcite and aragonite, the amount of magnesium ions required to make the Gibbs free energy of magnesium-substituted calcite higher than that of aragonite is calculated, as shown in Equation (2).

[0045] (2) in, It is the difference in standard Gibbs free energy of formation between aragonite and calcite; It is the change in the standard Gibbs free energy of formation caused by the substitution of one mole of calcium element in calcium carbonate by one mole of magnesium element.

[0046] The content of free magnesium ions is a key factor affecting aragonite formation. The partial substitution of calcium ions by magnesium ions alters the thermodynamic properties of calcite. However, the complex chemical reactions occurring in cement systems make it difficult to obtain the free magnesium ion content in real time. Considering the above, calculating the phase composition and ion concentration in the system based on a thermodynamic model is a time-saving and effective method. The phase composition and ion concentration changes during the carbon mineralization process were calculated using the GEM SELEKTOR open-source program. CSHQ was used to simulate the amorphous hydrated calcium silicate gel phase (CSH). This model includes four CSH endmembers with Ca / Si ratios between 0.67 and 1.6, and two endmembers for K and Na, which can well simulate the CSH generated during the hydration of cementitious materials. Nitrogen was chosen to form the simulated atmosphere, which was further mixed with pure CO2 to create a gaseous environment with different CO2 concentrations. Compared to traditional dissolution and precipitation kinetic models, the thermodynamic model can account for all possible phases that may form, including the gel phase, which is often neglected in most cases.

[0047] The extended Debye-Hückel equation is used to calculate the activity coefficients of ions, as shown in equation (3).

[0048] (3) in and It is a coefficient characterizing the effects of pressure and temperature; It is a component The charge; It is the effective molar ionic strength; It is an ion size parameter; It is a semi-empirical parameter.

[0049] The free magnesium ion concentration calculated based on GEMS cannot be directly used to calculate the proportion of aragonite. Calcium carbonate formed during carbonization is layered onto the surface of the carbonatable phase (such as clinker), forming calcium carbonate clusters. Only magnesium ions entering the calcium carbonate clusters help to inhibit the transformation of aragonite into calcite. Considering that the density of the inner layer of calcium carbonate is higher than that of the newly formed outer layer of calcium carbonate, it is assumed that the rate of decrease in magnesium ion concentration is inversely proportional to its distance from the cluster center, as shown in equation (4).

[0050] (4) in, The distance between magnesium ions that diffuse into the calcium carbonate cluster and the surface of the calcium carbonate cluster; The ratio factor for the concentration of magnesium ions diffused into the interior of calcium carbonate clusters as a function of their diffusion depth.

[0051] By combining the boundary condition (5), the concentration of magnesium ions in the calcium carbonate cluster can be calculated, as shown in equation (6).

[0052] (5) (6) in, It is the diameter of the calcium carbonate cluster; It is the distance between the boundary of the aragonite and pure calcite layers and the center of the calcium carbonate cluster; It represents the concentration of free magnesium ions in the solution.

[0053] By combining the concentration distribution and the volume of the calcium carbonate clusters, the amount of effective magnesium ions in the clusters can be calculated, as shown in equation (7).

[0054] (7) in, It is the volume of the calcium carbonate cluster; The degree of magnesium ion penetration into calcium carbonate clusters is shown in equation (8). Studies have found that the process of magnesium ion entry into calcium carbonate is determined by the magnesium-to-calcium ratio in the solution, and that higher temperatures have a positive effect on increasing the magnesium ion content in calcium carbonate. Based on this, the relationship between the degree of penetration and the magnesium-to-calcium ratio and temperature is fitted.

[0055] (8) in, For temperature, [ [ ] represents the magnesium-to-calcium ratio in the solution.

[0056] Temperature affects not only the effective magnesium ion concentration but also the thermodynamic parameters themselves. According to the Harper equation, the Gibbs free energy change of the aragonite-calcite crystal transformation with temperature is calculated as shown in equation (9).

[0057] (9) in For temperature The Gibbs free energy change in the transformation of quartz into calcite; It is the enthalpy change of aragonite transforming into calcite; , and These are the differences in heat capacity coefficients between aragonite and calcite, respectively. The relationship between heat capacity and temperature can be calculated using equation (10). Based on this, the enthalpy change of aragonite in its transformation into calcite can be calculated using equation (11).

[0058] (10) (11) in, It is heat capacity; , , , It is the coefficient of heat capacity as a function of temperature; It is the enthalpy change of the aragonite to calcite transformation reaction at a temperature of 298K.

[0059] Composition unit Contribution factor to the standard Gibbs free energy of calcium carbonate The change with temperature can be calculated using equations (12) and (13) based on the coefficients under standard conditions.

[0060] (12) (13) in, It is an entropy change; It is a constituent unit The entropy at a temperature of 298 K.

[0061] Based on the above formula and the phase composition calculated by GEMS, the aragonite ratio at different temperatures and initial magnesium ion concentrations can be calculated, as shown in Equation (14).

[0062] (14) in, It is the concentration of free magnesium ions; It is the volume of the solution after the carbonization reaction; This refers to the mass of calcium carbonate; these three parameters were calculated using GEMS. Thermodynamic coefficients. and It is calculated based on equations (12) and (13). It is the molar mass of CaCO3. It was calculated according to equation (8). Enthalpy change of aragonite to calcite It is calculated according to equations (9)-(11).

[0063] Example 2 When organic crystal form modifiers, such as alkanolamines, are used, the thermodynamic simulation calculation method for calcium carbonate crystal form regulation during carbon mineralization is as follows: Organic polymorph modifiers alter the critical nucleation energy of calcium carbonate by selectively adsorbing onto the crystal surface and changing its surface energy. Selective adsorption preferentially occurs on the aragonite surface parallel to the c-axis, inhibiting crystal growth in the direction perpendicular to the c-axis and preventing the transformation of aragonite into calcite. Therefore, the key to quantifying the polymorphic ratios of different calcium carbonate species lies in quantifying the effect of organic polymorph modifiers on the surface energy of calcium carbonate.

[0064] The classic method for calculating interfacial energy is to use experimental data to correlate the nucleation induction time of a specific precipitation reaction with surface energy. However, in cement systems with complex raw material compositions, the simultaneous occurrence of numerous hydration and carbonation reactions makes it very difficult to directly obtain the nucleation induction time of calcium carbonate. Thermodynamic models, by focusing only on the initial and final states of the reaction and ignoring the specific process, are not ideal for cement systems. Therefore, establishing a thermodynamic model to directly calculate the surface energy and proportion of polymorphs of calcium carbonate in the reaction products, bypassing the complex reaction process, is highly suitable.

[0065] In this invention, a simple approach to calculating the aragonite ratio in an organic regulator system is proposed, which is to calculate the ratio by dividing the effective organic regulator content adsorbed on the surface of calcium carbonate by the amount of organic regulator required to inhibit the conversion of one mole of aragonite into calcite, as shown in Equation (15).

[0066] (15) in, It is the amount of organic additives adsorbed on the surface of the calcium carbonate layer; It is the amount of organic matter required to produce one mole of aragonite; It is the total amount of calcium carbonate.

[0067] Currently, there are no studies on the adsorption of organic additives on the surface of calcium carbonate, a carbon mineralization product in cement-based materials. A significant reason for this is that hydrated calcium silicate gel (CSH) in cement-based materials adsorbs organic additives. However, hydrated calcium silicate gel is an amorphous phase, and CSH with different calcium-to-silicon ratios exhibits different microstructures and adsorption capacities. This invention, based on a thermodynamic model, proposes a solution considering gels with variable calcium-to-silicon ratios. It calculates the CSH content for different calcium-to-silicon ratios and establishes a method to evaluate the adsorption capacity based on changes in the calcium-to-silicon ratio (Ca / Si) and specific composition of CSH under different degrees of carbonation. This allows for an approximate quantification of the amount of organic crystal form modifiers adsorbed on the gel phase surface.

[0068] To characterize CSH gels with different calcium-to-silicon ratios, the CSHQ model was used, which divides CSH colloids into four end groups: CSHQ JenD (C 1.5 S 0.67 H 2.5), CSHQ JenH (C 1.33 SH 2.17 ), CSHQ-TobD (C 0.83 S 0.67 H 1.83 ) and CSHQTobH (C 0.67 SH 1.5 The chemical composition and thermodynamic parameters of the CSH are listed in Table 2. As carbonation proceeds, the high-calcium phase gradually transforms into the low-calcium phase. The Ca / Si ratio has a significant effect on the adsorption of organic additives on CSH. Studies have shown that as the Ca / Si ratio increases, the adsorption of small organic molecules on the CSH surface increases approximately linearly. Therefore, the surface coverage of a specific CSH can be estimated using Equation (16).

[0069] (16) in, It is a CSH terminator (e.g., CSH-TobH) surface coverage; It is the average surface coverage of CSH; It is the calcium-silicon ratio of CSH.

[0070] Based on this, the effective amount of organic additives adsorbed on the surface of calcium carbonate can be calculated using equation (17).

[0071] (17) in, The effective adsorption capacity of organic additives; This refers to the concentration of organic additives in the solution. The volume of the solution; This indicates different types of CSH. These represent TobH, TobD, JenH, and JenD, respectively.

[0072] Table 2 Chemical composition and thermodynamic parameters of different gel phases The remaining organic crystal form regulators, after being adsorbed by the gel phase, are adsorbed onto the surface of calcium carbonate at a specific coverage rate to play their role in crystal form regulation. The Temkin II model is chosen to calculate the coverage rate of organic matter on the calcium carbonate surface, as shown in Equation (18). The main reason is that the Temkin II model avoids the monolayer adsorption assumption and considers the heterogeneity of binding sites and the intermolecular interactions between adsorbate molecules.

[0073] (18) in, It is the surface coverage; It refers to the concentration of organic additives; It is the gas constant; It is temperature (K); It is the equilibrium binding constant (L / mol); It is the adsorption energy (kJ / mol).

[0074] Given the high water-to-solid ratio in wet carbonation systems, a significant portion of calcium carbonate may precipitate separately, making solution supersaturation a key factor determining its surface area. It has been observed that under certain low supersaturation conditions, calcium carbonate growth is relatively slow or even incomplete, significantly impacting surface area. Existing research has found that relative supersaturation is a key parameter affecting surface area, exhibiting a power-law relationship. The relationship between actual and initial surface area can be approximated using equation (19).

[0075] (19) in, It is the actual surface area; It is the initial surface area; It is an empirical coefficient; It is the activity coefficient of a divalent ion.

[0076] Based on the idea of ​​formula (15), after calculating the content of effective crystal form regulator adsorbed on the surface of calcium carbonate, it is only necessary to further calculate the amount of organic matter required to generate one mole of aragonite to obtain the proportion of aragonite.

[0077] The amount of organic regulator required to produce one mole of aragonite It can be calculated using equation (20).

[0078] (20) in, It is the initial surface energy of aragonite; It is the critical surface energy (i.e., the surface energy of aragonite when the critical nucleation energies of aragonite and calcite are the same). It is the change in surface energy caused by 1 mol of organic additive.

[0079] The critical surface energy is calculated based on the condition that aragonite and calcite have the same critical nucleation energy. The critical nucleation energy is mainly affected by surface energy, temperature, supersaturation, and molecular volume. Among them, the surface energy containing the cubic term is the most critical influencing factor, and the relationship between them can be expressed by equation (21).

[0080] (twenty one) in, It is the critical nucleation energy; It is surface energy; It is the Boltzmann constant; It is the volume of molecules; It is the degree of supersaturation; it can be calculated using equation (22).

[0081] (twenty two) in, It is the supersaturation of calcium carbonate; It is the solubility product of calcium carbonate.

[0082] By combining equations (21) and (22), the value of the critical surface energy can be obtained. Furthermore, by considering the reduction in surface energy caused by the organic modifier, the specific proportion of aragonite can be calculated.

[0083] According to the theory of surface electrochemistry, the surface energy of an ionic crystal is determined by the surface energy of the crystal at the zero charge point and the surface charge of the ionic crystal, as shown in equation (23).

[0084] (twenty three) in, It is the surface energy at the point of zero charge; The change in surface energy is caused by the change in surface charge of the ionic crystal, which can be calculated according to equation (24).

[0085] (twenty four) in, It is the charge carried by the electrolyte; for calcium carbonate ; It is Faraday's constant; It is the gas constant; It is temperature (K); and These are the factors influencing surface energy, namely ion adsorption and point charge proximity to the surface. The addition of organic modifiers has a significant impact on the adsorption of surface ions. Specifically, the concentration of the organic modifier, the molar mass of the functional group, and the reactivity of the functional group with calcium ions determine the change in surface charge, as shown in Equation (25). Furthermore, due to the different shapes of different calcium carbonate polymorphs, the adsorption of organic modifiers also has different effects on their interfacial energy.

[0086] (25) in, It is the surface charge density. These are the maximum surface charge densities, which can be calculated using equations (26) and (27), respectively. It is the adsorption coefficient. It refers to the concentration of organic additives; The dissociation constant P of the organic additive Ka; It is the P of carbonic acid Ka ; It is the shape factor.

[0087] (26) (27) in, It is the lattice constant; It is Faraday's constant; It is ionic strength; It is the molar mass of calcium carbonate. It is Planck's constant; It is the surface potential.

[0088] The Debye constant is calculated using equation (28).

[0089] (28) in, It is the vacuum permittivity (F / m). It is the relative permittivity of the solvent.

[0090] Surface potential The result is calculated based on Nernst's law, as shown in equation (29).

[0091] (29) in, Represents a zero-charge state; This indicates the activity of a component in this state, which can be calculated from the equilibrium state of the crystal in pure water.

[0092] For shape factor Currently, there is no accurate calculation formula. Since the representative shapes of the three calcium carbonate polymorphs—calcium carbonate, aragonite, calcite, and aragonite—are spherical, cubic, and acicular, respectively, the lattice constants of different calcium carbonate polymorphs can be estimated using formula (30), such as... Figures 12-14 And as shown in Table 3.

[0093] (30) in, The shape factor, and is the lattice constant of calcium carbonate.

[0094] Table 3 Shape factors for different calcium carbonate crystal forms The effect of a point charge approaching the surface on the surface energy of calcium carbonate can be calculated using equation (31).

[0095] (31) in, It is Faraday's constant; It is ionic strength; It is the length of Debye; It is the surface charge density.

[0096] Overall, the model is constructed based on the idea that the aragonite content in the system equals the effective organic additive content acting on the calcium carbonate surface divided by the amount of organic additive required to thermodynamically inhibit the transformation of 1 mol of aragonite to calcite. Based on equations (16) to (19), the adsorption amount of organic additives relative to the CSH gel with a variable calcium-silicon ratio can be calculated, and the effective organic additive content acting on the calcium carbonate surface can be further calculated based on this. Based on equations (20) to (22), the critical surface energy at which the transformation between aragonite and calcite occurs can be calculated, while based on equations (23) to (31), the extent to which the organic modifier reduces the interfacial energy can be calculated. In this process, the shape of calcite and aragonite is the key factor leading to the difference in their interfacial energy changes, so their geometry is approximated and quantified in the model based on the lattice constant. The model calculations are performed using GEM SELEKTOR and MATLAB programs, the former being used to calculate the phase composition and ion concentration, and the latter being used to solve the numerical equations.

[0097] Considering that this invention includes both inorganic and organic crystal form regulators, Examples 3 and 4 will provide specific examples of these two scenarios. To measure the error of the calculation method, simulation calculations and experimental analyses will be performed simultaneously in each example, and the results will be compared. To further verify the reliability of the model, Example 5 also compares data from several existing literature studies with simulation calculation data performed under the same conditions using this invention.

[0098] Example 3 In this Example 3, the common inorganic crystal form regulator MgCl2 will be used to control the crystal form during the carbon mineralization process of cement slurry. The specific operation steps are as follows: (1) Prepare 200 ml of MgCl2 solutions with concentrations of 0, 0.05, 0.1, 0.125, 0.15, 0.175 and 0.25 mol / L using deionized water for later use.

[0099] (2) Weigh 20g of ordinary Portland cement and add it to a beaker containing the prepared MgCl2 solution. Then place the solution in a constant temperature water bath. The constant temperature water bath is used to control the temperature of the carbon mineralization reaction and to stir the cement slurry at a uniform speed. In this embodiment, four different temperature groups of 25℃, 40℃, 60℃ and 80℃ will be set respectively.

[0100] (3) Add a magnetic stirring rotor to the beaker and stir the cement slurry at a constant speed of 850 rpm. At the same time, introduce CO2 gas into the cement slurry at a constant speed of 0.5 Nl / min.

[0101] (4) After the reaction has proceeded for 60 minutes, turn off the CO2 gas, remove the beaker, and place it on a horizontal experimental platform for 10 minutes. After the supernatant and reaction product have separated into layers, use a syringe to extract the supernatant to obtain the wet carbonized sample.

[0102] (5) Place the wet carbonized sample in a high-speed centrifuge and centrifuge at 8000 rpm for 5 min. Remove the supernatant and centrifuge again. Repeat this process three times.

[0103] (6) After centrifugation, the sample was placed in a vacuum drying oven at 40°C and dried for 3 days, and then ground to obtain carbonized sample powder.

[0104] (7) The proportion of different calcium carbonate crystal forms in the carbonized sample powder was analyzed using X-ray diffraction and Rietveld quantitative methods. XRD measurements were performed using Cu kα X-ray radiation at 40 kV and 40 mA. The 2θ scan range was 3°–70°, the step size was 0.02°, and the rate was 2° / min. 20 wt% rutile (TiO2) was added to the sample powder as an internal standard. Rietveld quantitative analysis was performed using X'Pert Highscore Plus software (PANalytical 5.1).

[0105] (8) The chemical structures of different carbonization products were characterized using Fourier transform infrared spectroscopy (FTIR). A Thermo Scientific IS10 FTIR workstation was used, and KBr and carbonization powder samples were mixed and pressed into disk-shaped samples for FTIR measurements. The wavenumber range acquired was 500–4000 cm⁻¹. —1 Approximately 1 mg of sample powder was ground together with 100 mg of IR-grade KBr for 5 minutes and then pressed into thin discs. Each sample was pressed into a 2 cm disc. —1 The resolution was 32 scans.

[0106] (9) Thermogravimetric analysis (TG-DTG) was used to calculate the calcium carbonate content and CO2 absorption. The sample was ground into powder until it passed through a 300-mesh sieve. The powder was analyzed using a Netzsch STA 409PC thermal analyzer. For each test, approximately 15 mg of powder sample was weighed and placed in an aluminum crucible for heating. The test conditions were: heating from 30°C to 1000°C at a rate of 10°C / min under a nitrogen protective atmosphere.

[0107] The proportion of aragonite-type calcium carbonate obtained from the test varies with the concentration of magnesium chloride, as shown in the attached figure. Figure 2 As shown, the results obtained using thermodynamic calculations are also presented in the appendix. Figure 2 It can be observed that at 25℃, once the magnesium chloride concentration reaches the critical value of 0.08 mol / L (the concentration at which aragonite begins to form), the proportion of aragonite gradually increases with increasing magnesium chloride concentration. Increasing temperature lowers this critical concentration value. Furthermore, the saturation concentration (the concentration at which calcium carbonate is almost entirely composed of aragonite crystals) also decreases with increasing temperature, meaning that the magnesium chloride concentration required to obtain a carbonation product composed entirely of aragonite whiskers decreases. Moreover, it can be observed that the trends of the thermodynamic calculations and experimental results are consistent. The average error between the calculated and experimental results is 2.94%, demonstrating that this method can predict the proportion of calcium carbonate crystals in a carbonation system within a small error range.

[0108] To further verify the reliability of the calculation method, the changes in the proportion of aragonite-type calcium carbonate and the carbon dioxide absorption rate as the carbon dioxide input gradually increased were tested, as shown in the attached figure. Figure 3 and attached Figure 4 As shown. To more scientifically reflect the impact of carbon dioxide input on the carbonitridification degree of cement, the variable studied was the ratio of the mass of input carbon dioxide to the mass of cement, rather than the mass of input carbon dioxide alone. It can be observed that the experimental and calculated aragonite crystal form ratios show consistent trends, with an average error of 4.65%. Regarding carbon dioxide absorption rate, thermodynamic calculations also demonstrated relatively high accuracy, with an average relative error of 6.9%. (See Appendix...) Figure 4 The study also found that the thermodynamic model accurately predicted the conditions under which CO2 absorption rate began to decline rapidly (M(CO2) / M(PC) = 0.48). This inflection point may vary depending on the composition of cement raw materials and environmental conditions. Therefore, the model can help determine the appropriate CO2 input, thereby improving the efficiency of CO2 capture and preventing excessive carbon dioxide from escaping back into the atmosphere.

[0109] Example 4 In this Example 4, monoethanolamine (MEA), a common organic crystal form regulator, will be used to control the crystal form during the carbon mineralization process of cement slurry. The MEA used (AR, 99%, CAS: 141-43-5) is of analytical grade. The specific operating steps are as follows: (1) Prepare 200 ml of MEA solutions with concentrations of 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5 and 4.0 mol / L using deionized water for later use.

[0110] (2) Weigh 20g of ordinary Portland cement and add it to a beaker containing the prepared MEA solution. Then place the solution in a constant temperature water bath. Five different temperature groups were set: 40℃, 50℃, 60℃, 70℃, and 80℃.

[0111] (3) Add a magnetic stirring rotor to the beaker and stir the cement slurry at a constant speed of 850 rpm. At the same time, introduce CO2 gas into the cement slurry at a constant speed of 0.5 Nl / min.

[0112] (4) After the reaction has proceeded for 60 minutes, turn off the CO2 gas, remove the beaker, and place it on a horizontal experimental platform for 10 minutes. After the supernatant and reaction product have separated into layers, use a syringe to extract the supernatant to obtain the wet carbonized sample.

[0113] (5) Place the wet carbonized sample in a high-speed centrifuge and centrifuge at 8000 rpm for 5 min. Remove the supernatant and centrifuge again. Repeat this process three times.

[0114] (6) After centrifugation, the sample was placed in a vacuum drying oven at 40°C and dried for 3 days, and then ground to obtain carbonized sample powder.

[0115] The sample testing method in Example 4 was the same as in Example 3. The proportion of aragonite-type calcium carbonate under different organic crystal form concentrations and at different temperatures is shown in the attached figure. Figure 5 and attached Figure 6 As shown, the calculated results are quite close to the experimental results, with average errors of 3.71% and 4.52% for different concentration groups and temperature groups, respectively.

[0116] Example 5 In this embodiment 5, existing literature data was compared with simulation calculation data performed under the same conditions using the present invention. The specific implementation steps are as follows: (1) Relevant literature search. In this embodiment, the results of four literature articles using magnesium ions as crystal form regulators and eight literature articles using organic compounds as crystal form regulators were statistically analyzed. Considering the diversity of organic compounds, the seven literature articles analyzed in this embodiment used three organic compounds with different functional groups than monoethanolamine: polyacrylic acid (PAA), polyacrylamide (PAM), and polyacryl alcohol (PAV).

[0117] (2) Statistical analysis of literature data. The main statistical dimensions include: raw material composition, purity of crystal form regulator, concentration of crystal form regulator, temperature, pressure, carbon dioxide concentration, and proportion of aragonite-type calcium carbonate.

[0118] (3) Use the statistical literature data as input for model calculation. Unify the units of input parameters, including inputting the composition of raw materials as oxide composition, the purity of crystal form regulator as percentage purity, the concentration as mol / L, the temperature as ℃, the pressure as KPa, the carbon dioxide concentration as percentage concentration, and the aragonite crystal form calcium carbonate as percentage ratio.

[0119] (4) Perform model calculations. The calculation program in the specific implementation method is used to calculate the input data of each literature to obtain the proportion of aragonite-type calcium carbonate, and the results are compared and analyzed with those in the literature.

[0120] A comparison of literature data and simulation calculation data is attached. Figures 7-11 As shown, under varying amounts of magnesium chloride, polyacrylic acid, polyacrylamide, and polyacrylamide, as well as temperature variations, the average errors between the literature results and the calculated results were 8.86%, 3.95%, 7.77%, 6.65%, and 6.70%, respectively.

[0121] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or system that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or system. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or system that includes that element.

[0122] Furthermore, it should be noted that the scope of the methods and systems in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.

[0123] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the scope of protection of the present invention, and all of these forms are within the protection scope of the present invention.

Claims

1. A thermodynamic simulation calculation method for the regulation of calcium carbonate crystal form during carbon mineralization, characterized in that, Includes the following steps: Step S1: Determine the initial conditions, including the oxide composition of the cement-based material, the amount of carbon dioxide input, the temperature, and the concentration of the crystal form regulator; Step S2: Correct the effects of temperature and ion doping on the thermodynamic data of calcium carbonate crystal form and establish a thermodynamic database; Step S3: Based on the principle of minimizing Gibbs free energy, calculate the solid composition, ion concentration, pH change and porosity of the carbon mineralization products of cement-based materials. Step S4: Calculate the effect of the crystal form regulator on the bulk free energy and surface free energy of calcium carbonate crystal form; Step S5: Calculate the proportion of calcium carbonate crystal form in the carbon mineralization product.

2. The method according to claim 1, characterized in that, In step S1, the crystal form regulators include inorganic regulators represented by magnesium salts and organic regulators represented by alkanolamines.

3. The method according to claim 1, characterized in that, In step S2, the calcium carbonate crystal forms include calcite, aragonite, and spherulite.

4. The method according to claim 1, characterized in that, In step S2, the thermodynamic database is established based on the following method: The database uses a combination of PSI / Nagra and Cerndata18 open-source databases. The Gibbs generation free energy and enthalpy of formation of calcite and aragonite partially substituted with magnesium ions were quantified by combining basic polyhedral units. The Gibbs generation free energy of calcite and aragonite as a function of temperature was calculated based on the Harper equation.

5. The method according to claim 4, characterized in that, In step S3, the solid phase composition and ion concentration were calculated using the open-source thermodynamic software GEM SELEKTOR, and the final generated phase was determined by minimizing the Gibbs free energy. The solid phase composition includes mass variations of calcite, aragonite, silica gel, hydrated magnesium silicate gel, magnesium calcite, ferrophosphate, and kaolinite. The ion concentration includes Ca in the liquid phase. 2+ Mg 2+ K + Na + CO3 2- HCO3 - SO4 2- OH - H + Mg(HCO3) + Ca(HCO3) + Ca(HSiO3) + The concentration change.

6. The method according to claim 1, characterized in that, When the crystal form regulator is an inorganic regulator, step S4 includes: Calculate the change in volume free energy caused by magnesium ion substitution for calcium ions in calcite; The effective magnesium ion concentration in calcium carbonate clusters was calculated. The relationship between the degree of penetration and the magnesium-to-calcium ratio and temperature was fitted.

7. The method according to claim 1, characterized in that, When the crystal form regulator is an organic regulator, step S4 includes: The adsorption capacity of organic regulators on CSH gels with different calcium-to-silicon ratios was quantified using the CSHQ model. The effect of calcium carbonate layer thickness on adsorption coverage was corrected based on the Temkin II adsorption model. The effects of organic modifiers on surface energy and critical nucleation energy were calculated.

8. The method according to any one of claims 1-7, characterized in that, The method described above is applicable to controlling the total amount and relative proportion of calcite, aragonite and aragonite in carbon mineralization products, so as to improve the flexural strength and toughness of carbon mineralization products.

Citation Information

Patent Citations

  • Additive for blended cement compositions, cement produced therefrom and methods related thereto

    WO2020099877A1